APLIKASI PUPUK KOHE KAMBING YANG DIFERMENTASI DENGAN BIOAKTIVATOR Streptomyces sp. DALAM MENGENDALIKAN PENYAKIT BERCAK UNGU DAN MATI PUCUK PADA TANAMAN BAWANG PUTIH (Allium sativum L) - Damayanti , Elsa; Haryanto, Hery; Muthahanas, Irwan (Journal of Microbiology, Biotechnology and Conservation, 2025)
This study aims to determine whether the application of fermented goat manure with Streptomyces sp. bioactivator can control purple blotch (Alternaria porri) and top dieback (Phytophthora porri) diseases in garlic plants (Allium sativum L). The research was conducted at the Microbiology Laboratory of the Faculty of Agriculture, University of Mataram, and on a farmer's paddy field located in Sembalun Bumbung Village, East Lombok Regency. The study was carried out from May to November 2024. The experimental design used in this study was a Completely Randomized Design (CRD) consisting of six treatments: P0 (no fertilizer), P1 (goat manure without bioactivator), P2 (goat manure + SH isolate), P3 (goat manure + BSi isolate), P4 (goat manure + BSc isolate), and P5 (goat manure + SH isolate + liquid SH). Each treatment was repeated six times, resulting in 36 experimental units/plots. The data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level, followed by the Honest Significant Difference (HSD) test at a 5% significance level. The results showed that applying fermented goat manure with Streptomyces sp. bioactivator affected the growth of garlic plants but did not affect the yield of garlic plants (Allium sativum L). The treatment with goat manure + BSi isolate (P3) showed the highest value in plant growth, while the treatment with goat manure + SH isolate + liquid SH (P5) showed the highest yield. Meanwhile, the incidence of purple blotch disease was not affected by the application of fermented goat manure with Streptomyces sp., but it successfully reduced the incidence of top dieback disease in garlic plants.